Laplace transform effectiveness in the M|G|∞ queue busy period probabilistic study - Ferreira, M. A. M. (2021)
The Laplace transform is a widely used tool in the study of probability distributions, often allowing for a probability density functions and distribution functions simpler determination and being a “moments generating function”. In this paper, it is considered a situation not so simple, as it is the case of the M|G|∞ queue busy period length distribution. Attention will also be given the respective tail Laplace transform. Then, in the context of an open queues network, which nodes behave as M|G|∞ queues, the Laplace transform will be used to construct an algorithm to determine the Laplace transform of the global service time length of a customer during their stay on the network distribution.